Determinants of the euro real effective exchange rate: a BEER/PEER approach - Francisco Maeso-Fernandez; Chiara Osbat; Bernd Schnatz (European Central Bank (ECB), 2001)
This paper presents an empirical analysis of the medium-term determinants of the euro effective exchange rate. The empirical analysis builds on synthetic quarterly data from 1975 to 1998, and derives a Behavioural Equilibrium Exchange Rate (BEER) and a Permanent Equilibrium Exchange Rate (PEER). Four different model specifications are retained, due to the difficulties encountered in specifying an encompassing model. Results indicate that differentials in real interest rates and productivity, and (in some specifications) the relative fiscal stance and the real price of oil, have a significant influence on the euro effective exchange rate. Assessing the existence and the extent of the over- or undervaluation of the exchange rate is not straightforward, since these different specifications often lead to contrasting findings. However, all four models point unambiguously to the undervaluation of the euro in 2000, although the extent of this undervaluation largely depends on the specification chosen
Keywords: F31; F32; 330